A literature review on road surface marking materials and retroreflectivity properties - Metin Mutlu Aydın (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2017)
Urban and rural roads are opened to service after the application of road surface markings in Turkey. However, visibility of these roads reduce or disappear caused by the disrepair in a short time after the construction. These road surface markings have a mission to be a visual guide on behavior of lane utilization of drivers. For this reason, it has crucial importance to prevent traffic accidents. Unfortunately, the necessary importance to road surface markings are not given by the authorities in urban and rural roads of Turkey. Generally, standard road marking paint are used in all roads because of its low price and it loses retroreflectivity performance after short time. As a result of this situation chaos, lane indiscipline and many traffic accidents occur in urban and rural roads. Whereas, many different road painting materials are used such as Epoxy, Methyl Methacrylate, Polyester, Thermoplastic, Polyurea etc. to obtain higher performance and resistance according to different road characteristics and environmental conditions. In the scope of this study, a general information were given about the utilization of different surface marking materials which is used in developed countries effectively. Additionally, a number of recommendations and guidance notes have been provided for road makers and decision authorities wishing to use these materials in Turkey.